SERVICES INDUSTRY MANAGEMENT IN UZBEKISTAN - Bazarova Fayyoza Tukhtamurodovna (Galaxy International Interdisciplinary Research Journal, 2023)
The article studies and analyzes the management of the service sector in our country, its features, development, main groups and new service sectors in our society.